2021
DOI: 10.1093/chemse/bjab006
|View full text |Cite
|
Sign up to set email alerts
|

Six-Month Psychophysical Evaluation of Olfactory Dysfunction in Patients with COVID-19

Abstract: This study prospectively assessed the six-month prevalence of self-reported and psychophysically measured olfactory dysfunction in subjects with mild-to-moderate COVID-19. Self-reported smell or taste impairment was prospectively evaluated by SNOT-22 at diagnosis, 4-week, 8-week, and 6-month. At 6 months from the diagnosis, psychophysical evaluation of olfactory function was also performed using the 34-item culturally adapted University of Pennsylvania Smell Identification Test (CA-UPSIT). 145 completed both t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
123
4
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 116 publications
(139 citation statements)
references
References 36 publications
10
123
4
2
Order By: Relevance
“… 96 , 97 Although a definitive link between chronic or permanent olfactory impairment and future neurological vulnerability cannot yet be made, some studies suggest an association. 40 , 41 , 42 , 54 , 55 , 98 , 99 …”
Section: Discussionmentioning
confidence: 99%
“… 96 , 97 Although a definitive link between chronic or permanent olfactory impairment and future neurological vulnerability cannot yet be made, some studies suggest an association. 40 , 41 , 42 , 54 , 55 , 98 , 99 …”
Section: Discussionmentioning
confidence: 99%
“…In our study, patients were evaluated within the first 10 days of symptom onset, when olfactory dysfunction should not yet have begun to recover [ 29 , 30 ]. At this early stage of COVID-19, 74.3% of patients had olfactory dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…We analysed 202 patients with positive COVID-19 swabs and showed that 65% reported smell and taste alterations in addition to the other ENT symptoms reported above 23 . These patients were reviewed 4 weeks after onset of their sensory changes: 50% m recovered completely, 40% had improvement and 10% had unchanged or worsened symptoms [24][25][26] . Reports from a different study on household members with positive COV-ID-19 swabs found that 38% showed typical COVID-19 symptoms and 22% had these symptoms in association with altered sense of smell and taste, while 4% only had alteration of smell and taste as an isolated symptom 27 .…”
Section: Discussionmentioning
confidence: 99%